Durability of Alkali-Activated Materials Made with a High-Calcium, Basic Slag - Pavia, Sara (My University, 2021)
Alkali activated (AA) materials have been investigated for decades as an alternative to Portland cement (PC) products. Most consist of a silicate waste activated with alkalis, which leads to lower green-house gas emissions and a substantial drop in the use of unrenewable material resources. This paper studies the durability of AA materials made with a ground granulated blast furnace slag (GGBS) from Dublin, activated with sodium hydroxide (NaOH), and sodium silicate (Na2SiO3), both combined and separately, and cured at 20 and 60°C. The long-term strength and durability were assessed with accelerated weathering tests using thermal-moisture cycling, salt crystallization and freeze-thaw cycling. The 28-day strengths are compared to the 270-day strengths. The mass loss and macro/microscopic changes were investigated. The slag complies with standard requirements being ultra-fine (SSA=1950 m2/kg), basic (1.56 basicity-CaO+ MgO/SiO2) and highly amorphous. It is adequate for alkali activation, having a CaO/SiO2 ratio of 1.41 and a Al2O3/SiO2 ratio of 0.34. Melilite is the main constituent of the slag, in an isomorphous solid solution with gehlenite as the end member. The results evidenced that mechanical strength is not compromised over time, but it tends to significantly increase between 28 and 270 days. Despite the exaggerated weathering conditions of the laboratory cycling, the strength loss and micro/macro damage after cycling is minimum, except for a few of the Na2SiO3 activated slag specimens. The Na2SiO3+NaOH activated GGBS materials showed the greatest resilience to the effects of frost, thermal/moisture and salts, as they remained intact and showed the greatest strenghts after cycling, and an unaltered microstructure consisting of unreacted GGBS and scattered silica cements alternating with alumino-silicates. In contrast, both the NaOH and the Na2SiO3 activated GGBS materials were slightly damaged displaying salt efflorescence and microcracks. Increasing the curing temperature does not increase the durability of the AA slag specimens as it doesn’t significantly enhance the late mechanical strength. However, it slightly improves the strengths of the Na2SiO3+NaOH and NaOH activated mixes but lowers the strengths of the Na2SiO3 specimens.
PUBLISHED
Keywords: Alkali activation; GGBS; Durability; Strength